Aftermath - Armstrong, Kelley; OverDrive, Inc. (New York : Crown, 2018)
"Three years after losing her brother Luka in a school shooting, Skye Gilchrist is moving home. But there's no sympathy for Skye and her family because Luka wasn't a victim; he was a shooter. Jesse Mandal knows all too well that the scars of the past don't heal easily. The shooting cost Jesse his brother and his best friend--Skye. Ripped apart by tragedy, Jesse and Skye can't resist reopening the mysteries of their past. But old wounds hide darker secrets. And the closer Skye and Jesse get to the truth of what happened that day, the closer they get to a new killer." --.
Electronic book.
Electronic reproduction.
Keywords: School shootings -- Juvenile fiction; Brothers -- Juvenile fiction -- Death; High school students -- Juvenile fiction; Best friends -- Juvenile fiction; Mass murder investigation -- Juvenile fiction; Teenagers -- Juvenile fiction; School shootings -- Fiction; School shootings -- Juvenile fiction; School shootings -- Fiction; Best friends -- Fiction; Best friends -- Fiction; High school students -- Fiction; High school students -- Juvenile fiction; YOUNG ADULT FICTION / Family / Siblings; YOUNG ADULT FICTION / Romance; YOUNG ADULT FICTION / Thrillers & Suspense; Best friends. -- Juvenile fiction; Brothers -- Death; High school students. -- Fiction; Mass murder investigation; School shootings; Teenagers; Brothers -- Death -- Fiction; Friendship -- Fiction; Mass murder investigation -- Fiction; Teenagers -- Fiction; Best friends; High school students; Advantage title -- Fiction; Detective and mystery fiction; Fiction; Juvenile works; Young adult works; Electronic books; Young adult fiction; Detective fiction; Mystery fiction